2014
DOI: 10.1007/s10803-014-2120-z
|View full text |Cite
|
Sign up to set email alerts
|

Is the Ability to Integrate Parts into Wholes Affected in Autism Spectrum Disorder?

Abstract: There is considerable debate about whether people with autism spectrum disorder (ASD) are biased toward local information and whether this disrupts their ability to integrate two complex shapes elements into a single figure. Moreover, few have examined the relationship between integration ability and ASD symptom severity. Adolescent/adult males with ASD and age and IQ-matched controls were compared on their performance of a simple silhouette-to-shape matching task and a higher-order shape-integration task. Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Performance consistent with the weak central coherence hypothesis has been observed in individuals with ASD on verbal [18,24,25,[46][47][48], as well as non-verbal [49][50][51][52][53][54] tasks. In fact, some have suggested that this local bias is a core component of the ASD phenotype [55,56].…”
Section: Global-local Processing In Asdsupporting
confidence: 72%
“…Performance consistent with the weak central coherence hypothesis has been observed in individuals with ASD on verbal [18,24,25,[46][47][48], as well as non-verbal [49][50][51][52][53][54] tasks. In fact, some have suggested that this local bias is a core component of the ASD phenotype [55,56].…”
Section: Global-local Processing In Asdsupporting
confidence: 72%
“…People with a locally coherent processing style have trouble making integrated wholes out of the sum of parts and coherent stories out of disconnected strings of events; they have difficulty seeing the forest for the trees. Researcher Uta Frith has memorably described the consequences of local coherence as “an incoherent world of fragmented experience” (1989, see also Olu-Lafe et al, 2014). Problems inferring the motivations of other people can make human behavior seem capricious, incomprehensible, and utterly unpredictable.…”
Section: The Need For External Structure In Autism Spectrum Conditionsmentioning
confidence: 99%
“…In addition, the experimental task focused on the production of novel words. To be included in the ASD group, each participant had an independent diagnosis of ASD (disclosed via parent report) and obtained a score on the Autism Diagnostic Observation Schedule‐Second Edition (ADOS‐2; Lord et al., ) that met cut‐offs for either autism or autism spectrum (McGregor & Bean, ; Olu‐Lafe, Liederman, & Tager‐Flusberg, ). To be included in the TD group, each child attained a standard score of 85 or higher on the Structured Photographic Expressive Language Test‐3rd Edition (Dawson, Stout, & Eyer, ) or the core battery of the Clinical Evaluation of Language Fundamentals – 4 (Semel, Wiig, & Secord, ), whichever was age appropriate.…”
Section: Methodsmentioning
confidence: 99%